Ibuprofen, a traditional drug that may impact the course of COVID-19 new effective formulation in nebulizable solution - García Canclini, Néstor (2020)
Fil: García Canclini, Néstor. Consejo Nacional de Investigaciones Científicas y Técnicas de Argentina. Instituto de Investigaciones en Ciencias de la Salud; Argentina.